Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/rheumatology/kez037
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy is associated with treatment response and serious adverse events: results from the British Society for Rheumatology Biologics Register for Rheumatoid Arthritis

Abstract: Objective To evaluate whether polypharmacy is associated with treatment response and serious adverse events (SAEs) in patients with RA using data from the British Society for Rheumatology Biologics Register (BSRBR-RA). Methods The BSRBR-RA is a prospective observational cohort study of biologic therapy starters and a DMARD comparator arm. A logistic regression model was used to calculate the odds of a EULAR ‘good response’ af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
0
17
0
1
Order By: Relevance
“…Whereas, at the first visit women took more medications than men, both women and men had more medications at the last visit. Also in the SLR, polypharmacy is reported to be associated with age, whereas results are inconclusive for the gender association (6,20,23).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Whereas, at the first visit women took more medications than men, both women and men had more medications at the last visit. Also in the SLR, polypharmacy is reported to be associated with age, whereas results are inconclusive for the gender association (6,20,23).…”
Section: Discussionmentioning
confidence: 96%
“…The question, how much the intake of multiple medications with possible interactions harms the patient more than provides a benefit, and reduces the patients' compliance, is still unanswered. Bechman et al (23) addressed two aspects of polypharmacy in his paper. The aspect of serious adverse events (SAE) could not be assessed in the Innsbruck cohort, as SAEs did not occur within the observational period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in rheumatoid arthritis cohorts show that patients with rheumatoid arthritis tend to have polypharmacy (median number of drugs approximately 5) and, further, that older age tends to increase the risk for polypharmacy (65,66). Other studies have also shown polypharmacy to be a predictor of adverse outcomes in rheumatoid arthritis (67). For example, higher use of corticosteroids, irrespective of disease activity, has been associated with poor outcomes in rheumatoid arthritis (68–71).…”
Section: Discussionmentioning
confidence: 99%